D-dimer for the diagnosis of upper extremity deep and superficial venous thrombosis. Issue 4 (April 2015) - Sartori, Michelangelo; Migliaccio, Ludovica; Favaretto, Elisabetta; Cini, Michela; Legnani, Cristina; Palareti, Gualtiero; Cosmi, Benilde
Abstract Background D-dimer role is well established in the diagnostic work-up for lower limb deep vein thrombosis (DVT), however it has not been formally tested for clinically suspected upper extremity DVT and/or superficial vein thrombosis (SVT). Aim To ascertain D-dimer diagnostic accuracy for upper extremity DVT and/or SVT. Study design We performed a single centre management study in outpatients referred by emergency or primary care physicians for clinically suspected upper extremity DVT. All patients underwent D-dimer testing (cut-off value: ≤ 500 ng/mL), and a B-mode and color Doppler ultrasonography examination. In case of either technical problems or anatomical barriers, ultrasonography was repeated after 5-7 days. All patients were followed up for three months for the occurrence of symptomatic DVT and/or SVT and/or pulmonary embolism. Results We enrolled 239 patients (F: 63.6%; mean ± SD age: 58.3 ± 16.8). At the initial diagnostic work-up, DVT was detected in 24 (10%) patients while SVT in 35 (14.6%) patients. During follow-up, one upper extremity DVT was found. D-dimer levels were higher in patients with DVT than in those without. Sensitivity and specificity of D-dimer for DVT were 92% (95%CI: 73-99%) and 60% (95%CI: 52-67%) respectively, with a negative predictive value of 98% (95%CI: 93-100%), whereas for SVT they were 77% (95%CI: 59-89%) and 60% (95%CI: 52-67%) respectively, with a negative predictive value of 93% (95%CI: 86-97%). Conclusions D-dimer has a negative predictive value ≥ 93% for excluding DVT in symptomatic outpatients and it can be a useful test in the diagnostic work-up of suspected upper extremity DVT.